The Impact of Management by Walking Around on the Strategic Renewal of Business Organizations (Field Research in a Sample of Excellent grade hotels - in Baghdad) - Fadel Ibrahim, Maha; Awad Al-kubaisy , Salah Aldeen (Journal of Economics and Administrative Sciences, 2022)
This work aims to show the nature of the relationship between management by walking around  (the independent variable) and strategic renewal (the dependent variable), as well as it shows the effect of the independent variable on the dependent variable. Questionnaire items were considered the main tool for data collection by three basic aspects. The first involved the personal data of the respondents, while the second included items related to management by walking in five dimensions, and the third is strategic renewal items by addressing four dimensions. The tourism sector, while the community has six Excellent grade hotels was taken into account in this work which is rare in this field. Data was collected from a sample of (99) managers working in (6) hotels of the (excellent) category in Baghdad, which are (Al-Rasheed Hotel, Ishtar Hotel, Meridian Hotel, Al-Mansour Hotel, Babel Hotel, and Baghdad Hotel). Statistical analysis was performed using AMOS statistical software. The most important results presented a low level of the developmental and creative dimension, as they did not receive the same appreciation as the rest of the other dimensions. This means that the practice of walking by managers did not lead to development and creativity, and this may be due to neglecting the role of talented and creative workers. This research came out with results that could be a guide for the manager in the hotel and tourism sector in how to employ management by walking in the strategic renovation of hotels. The study also reflects the importance of walking management and provides the required support for its practice and development, especially in the hotel sector in the Iraqi and Arab environments.Paper type: Research paper